Interfacial properties in the CFRP and CFRP-Ti composites under hygrothermal conditions - Yu, Bin (2016)
Carbon fiber-reinforced plastic (CFRP) based composite riser integrated with titanium liner (namely CFRP-Ti composite riser) is a promising choice for deep-water oil exploration and production to replace conventional metal risers due to its various advantages including lightweight, high specific strength and stiffness, and outstanding corrosion resistance, etc. In achieving optimal performance of this hybrid composite system, interfaces in the composite system play a critical role, which include fiber-matrix interface, interlaminar interface, and metal-composite interface (MCI). Therefore, good tuning of these interfaces determines overall performance of the hybrid composite system. To improve the interfacial properties of the CFRP-Ti composites, two different strategies have been adopted in this work: i) modification of the interfaces in CFRPs and ii) tuning of the MCI via surface treatment of titanium alloy. Multiwalled carbon nanotubes (MWCNTs) are incorporated into silane coating and applied onto carbon fiber surface to enhance the interfacial bonding in CFRPs. The results of microbond tests show that the interfacial shear strength (IFSS) of prepared multi-scale phase reinforced composite (MPRC) can be significantly increased in comparison with that of common composite. It is observed that densification of CNTs forest within the interphase between carbon fiber and matrix during forming of nano-composite coating can lead to a high volume fraction of CNTs within the interphase and augment effects of interface-interlocking, which makes the coating-modification method a more efficient way than traditional matrix-tuning method for improving interfacial bonding. Long-term interfacial performance of the prepared hybrid composite in environments under fresh water and sea water has been studied based on single fiber microbond tests. IFSS of the MPRC is found to decrease with immersion time, just like common composite. However, carbon nanotube-modified silane coating well maintains its improvement effect on interfacial performance during a 120-day immersion test in both de-ionized water and simulated seawater. Interlaminar properties of CFRPs are also characterized and results show that glass transition temperature (Tg), interlaminar shear strength (ILSS), mode I and mode II interlaminar fracture toughness of laminates decrease under hygrothermal environment. However, silane treatment can improve the interlaminar fracture toughness of laminates, and incorporation of MWCNTs can further enhance these interlaminar properties even under hygrothermal environment. Surface of titanium alloy is anodized using mixture of NaOH, Na2C4H4O6•2H2O and EDTA as electrolyte. Anodization treatment can create nano-structured metal surfaces to substantially increase bonding area along interface. And the generated oxide layer has potential to react with epoxy by forming organo-metallic complex, facilitating wetting of titanium alloy surface by epoxy resin. Mechanical testing results show that this eco-friendly surface treatment on titanium alloy is quite effective to improve interlaminar fracture toughness of CFRP-Ti composites, as well as compressive properties of CFRP-Ti composite risers. Furthermore, according to the experimental study in hygrothermal environment, the surface treatments introduced in this work are found to maintain their improvement effects on hygrothermal resistance of the CFRP-Ti composites and result in considerably enhanced interlaminar properties.